2010
DOI: 10.1007/s11552-010-9277-5
|View full text |Cite
|
Sign up to set email alerts
|

Low-Grade Fibromyxoid Sarcoma of the Hand: A Case Report

Abstract: We report a case of low-grade fibromyxoid sarcoma with giant collagen rosettes in the hand of a 21-year-old female. This is a clinically and radiological benign appearing tumor that has a high rate of recurrence and metastasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Superficial angiomyxomas have a lobular appearance and are purely myxoid, lacking the collagenous component of the stroma of acral fibromyxoma. Superficial examples of LGFMS very rarely arise in the digits, have a mixed fascicular and whirling growth pattern and often more abrupt transition from myxoid to fibrous areas. LGFMS is also consistently positive for MUC4, which is both very sensitive and specific for this diagnosis.…”
Section: Acral Fibromyxomamentioning
confidence: 99%
“…Superficial angiomyxomas have a lobular appearance and are purely myxoid, lacking the collagenous component of the stroma of acral fibromyxoma. Superficial examples of LGFMS very rarely arise in the digits, have a mixed fascicular and whirling growth pattern and often more abrupt transition from myxoid to fibrous areas. LGFMS is also consistently positive for MUC4, which is both very sensitive and specific for this diagnosis.…”
Section: Acral Fibromyxomamentioning
confidence: 99%
“…4 Wide excision with negative margins has been shown to help to avoid local recurrence. 24,25 Negative margins are the most critical component in treating LGFMS and should not be sacrificed to preserve function or for radiation therapy. 29 In our review, one case with a positive margin after excision reported a recurrence after 5 months, supporting this notion.…”
Section: Discussionmentioning
confidence: 99%
“…Involvement of acral sites is not highly emphasized in the literature. After encountering this case, we reviewed the literature and found 24 cases (mostly embedded in case series) of LGFMS involving distal extremities and acral sites (Table ) …”
Section: Discussionmentioning
confidence: 99%